2016
DOI: 10.1242/dev.143743
|View full text |Cite
|
Sign up to set email alerts
|

Two new competing pathways establish the threshold for cyclin-B–Cdk1 activation at the meiotic G2/M transition

Abstract: Extracellular ligands control biological phenomena. Cells distinguish physiological stimuli from weak noise stimuli by establishing a ligandconcentration threshold. Hormonal control of the meiotic G2/M transition in oocytes is essential for reproduction. However, the mechanism for threshold establishment is unclear. In starfish oocytes, maturation-inducing hormones activate the PI3K-Akt pathway through the G βγ complex of heterotrimeric G-proteins. Akt directly phosphorylates both Cdc25 phosphatase and Myt1 ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 42 publications
(59 reference statements)
1
6
0
Order By: Relevance
“…Consistent with this, using U2OS cell line treated with DIA-001, we showed that PARP cleavage was enhanced. We also show that cyclin A levels increase after treatment with DIA-001 but cyclin B level increase only slightly suggesting cell cycle progression through the S/G2 transition but arrested at the G2/M phase (15)(16)(17). Together, the data from our study indicates that treatment with DIA-001 may induce cell cycle arrest in G2 phase and apoptosis in cancer cells.…”
Section: Discussionsupporting
confidence: 61%
“…Consistent with this, using U2OS cell line treated with DIA-001, we showed that PARP cleavage was enhanced. We also show that cyclin A levels increase after treatment with DIA-001 but cyclin B level increase only slightly suggesting cell cycle progression through the S/G2 transition but arrested at the G2/M phase (15)(16)(17). Together, the data from our study indicates that treatment with DIA-001 may induce cell cycle arrest in G2 phase and apoptosis in cancer cells.…”
Section: Discussionsupporting
confidence: 61%
“…Hence, it seems that Plac1 knockdown affected both Akt and MPF activity. Of interest, in meiotic starfish oocytes, Akt directly phosphorylates both Cdc25 phosphatase and Myt1 kinase, which results in the activation of cyclin B-Cdk1 and meiosis resumption (40), further supporting to idea that the Akt pathway might the primary downstream signal of Plac1.…”
Section: Discussionmentioning
confidence: 72%
“…16 In vertebrate cells, the entry of MPF into the nucleus during prophase was thought to be essential for the induction and coordination of M-phase events. 30,31 During the mitosis, Akt may regulate the intracellular localization and activation of Cdc2 by phosphorylating Cdc25B. [32][33][34][35] In this study, we used SH-6, a specific inhibitor of pAkt1 (Ser473), to track the function of pAkt1 (Ser473) in the release of diplotene arrest of mouse oocytes.…”
Section: Discussionmentioning
confidence: 99%